NAVIGATING THE CHARACTER FOUNDATIONS OF ELEMENTARY SCHOOLS IN THE POST-DIGITAL ERA - Arif Yudi Asmara; Noor Alwiyah; Sukma Wisnu Pamungkas; Fauzi Annur; Inas Alifatus Salma (Universitas Islam Raden Rahmat Malang, 2026)
This study aims to identify the appropriate character foundations for implementation at the elementary school level. Furthermore, it explores how the selected character foundations are implemented in educational institutions. This is crucial given that character education in Indonesia is not fully implemented. The method used was library research, where researchers reviewed various existing literature, particularly books, journal articles, and other final materials. The results of this study indicate that there are three characters foundations that every elementary school must build: integrity (honesty and responsibility), empathy, and resilience. These three characters foundations are not only crucial to implement optimally, but also appropriate for elementary schools, align with the foundations for combating corruption in Indonesia, and contain simple elements. Therefore, educational institutions, particularly elementary schools, can mobilize all educators to implement these three characters foundations. Keywords: character education, elementary school/Islamic elementary school, integrity, empathy, resilience, corruption